Food service operations in NTU. - Liaw, Angela Chor Ping. (2008)
Students should enjoy an overall experience if NTU were to compete with world-class institutions. The meal experience is part of this overall experience. This report investigates how foreign dining services can be implemented locally, analyses how students and staff want existing foodservices to be changed and implications of introducing new improvements.